A Two-Level Desired Load Profile Tracking Algorithm for Electric Two-Wheeler Charging Stations - Huu, D. N.; Ngoc, V. N. (Engineering, Technology & Applied Science Research, 2021)
In Vietnam and in other developing countries, two-wheeled electric vehicles are potential alternatives to gasoline-powered motorbikes. The growth in the number of Electric Two-Wheelers (E2Ws) requires a large power demand of charging load. In addition, the increasing spread in the appearance and penetration of rooftop photovoltaic (PV) power systems, with their intermittence and uncertain nature, poses technical challenges that need to be addressed. The coordination of PV rooftop operation and EV charging may be an effective solution to meet the emerging load demand from EVs, increasing solar power penetration while minimizing the cost of grid reinforcement or possible upgrades. In this paper, a two-level desired load profile tracking algorithm for PV integrated electric bicycles/electric motorcycle charging stations is proposed with the purposes of load leveling, valley filling, and peak shaving. The simulation results show that the proposed algorithm is an effective solution, significantly improving the load profile, especially when compared with uncontrolled charging and constant charging power scheme.